Perlindungan Hukum Terhadap Perempuan Yang Menjadi Korban Kekerasan Dalam Rumah Tangga - Annisa Nur Muthmainnah; Asep Suherman (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
Violence is an act against someone, especially women, which results in physical, sexual, psychological misery or suffering and domestic neglect. Domestic violence is a social phenomenon that has been going on for a long time in some households in Indonesia. The impacts resulting from these acts of violence produce psychological impacts on women who are victims of domestic violence, for example victims feel anxious, afraid, depressed, always alert, constantly imagine seeing similar cases, often daydreaming, moody, crying easily, having difficulty sleeping, and even having nightmares. . Victims lose confidence to act because they feel helpless, lose interest in taking care of themselves, and lose courage in expressing opinions and acting. The aim of this research is to find out how effective legal protection is for women who are victims of domestic violence, and what the obstacles are. The analysis of legal materials used in this research is an analytical perspective which is a type of normative research, by finding legal rules, legal principles and legal doctrines by examining library materials or secondary data.